IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN PRESTASI BELAJAR SISWA SMA N 1BATANGHARI LAMPUNG TIMUR - Yuyun Yunita (Ri'ayah: Jurnal Sosial dan Keagamaan, 2020)
School-based management is a management concept in schools as a solution to improve the quality of education in Indonesia, the concept of School-Based Management is a management model that provides more autonomy to schools and encourages schools to make participatory decision-making to meet school quality needs or achieve goals quality of schools within the framework of national education. Management-based implementation is expected to improve student learning achievement. The implementation of school-based management in the I Batanghari state high school includes: planning, organizing, actuating, controlling processes. The implementation of school-based management has an indirect influence on student learning achievement primarily in the aspects of the teaching-learning process. So that the implementation of the concept of school-based management in the Batanghari state senior high school has a positive impact on improving student achievement. Improving student learning achievement because the implementation of school-based management is actually not small, but its contribution cannot be ignored. Push Factors; there is support from parties related to the importance of the development of education for community development, the demands of the community for quality education, increasing professionalism of teachers through training activities, complete infrastructure, coordination and good task division, complete administration, high work ethic for teachers and employees , high public trust, opportunities for teachers, laboratory staff, librarians to attend seminars, workshops, upgrades.